1984
DOI: 10.1139/v84-470
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a di-π-methane rearrangement in the photoisomerization of 2,3-benzo-7,8-dimethylbicyclo[4.2.0]octa-2,4,7-triene to 6,7-dimethylbenzotricyclo[3.3.0.02,8]octa-3,6-diene

Abstract: , 2769 (1984). The direct and sensitized (Michler's ketone) irradiations of 2,3-benzo-7,8-dirnethylbicyc10[4.2.0]octa-2,4,7-triene (7) yield 6,7-dirnethylbenzotricycIo[3.3.0.02~X]octa-3,6-diene (3, @ = 0.030 and 0.093, respectively) and naphthalene (@ = 0.10 and 0.16, respectively). Deuterium labelling studies suggest that 3 derives from a Zimrnerrnan di-7-methane rearrangement of 7, and that 1,8-dimethyl-la,2,7,7a-tetrahydro-1,2,7-metheno-l H-cyclopropa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…When anisoles are examined as substrates, the formal cycloinsertion products, cyclooctatetraenocarboranes are isolated as the major products in addition to the minor [4 + 2] cycloaddition products (Scheme 13) [34]. It is noted that benzyne reacts with anisoles to generate exclusively the [4 + 2] cycloaddition products, which can be further transformed to benzocyclooctatetraenes by photolysis [35]. show that steric factors play a role in both regio-and chemo-selectivity, and electronic factors may also play an important role in the chemoselectivity as only the [4 + 2] cycloaddition reaction proceeds with toluene [34].…”
Section: With Anisolesmentioning
confidence: 99%
“…When anisoles are examined as substrates, the formal cycloinsertion products, cyclooctatetraenocarboranes are isolated as the major products in addition to the minor [4 + 2] cycloaddition products (Scheme 13) [34]. It is noted that benzyne reacts with anisoles to generate exclusively the [4 + 2] cycloaddition products, which can be further transformed to benzocyclooctatetraenes by photolysis [35]. show that steric factors play a role in both regio-and chemo-selectivity, and electronic factors may also play an important role in the chemoselectivity as only the [4 + 2] cycloaddition reaction proceeds with toluene [34].…”
Section: With Anisolesmentioning
confidence: 99%
“…On the other hand, benzyne reacts with anisoles to generate exclusively the [4 + 2] cycloaddition products, which can be further transformed to benzocyclooctatetraene by photolysis followed by the gas phase thermolysis process. 24 A plausible mechanism is proposed after the isolation and structural characterization of a [2 + 2] cycloaddition product from the reaction of o-carboryne with 2-methylanisole (Scheme 8). This [2 + 2] compound can be further transformed to cyclooctatetraenocarborane upon heating.…”
Section: Reaction With Anisolesmentioning
confidence: 99%
“…The results of deuterium-labelling experiments have shown that at least three routes can be used to generate the SB product, and in some cases their mode of formation has been shown to be multiplicity dependent, e.g., triene 7 gives SB 9 via a l,2-shift mechanism (route i, Scheme 2) from S,, but utilizes a Zimmerman di-'TFmethane rearrangement (DPM rearrangement) (20), which starts with the addition of benzyne to o-methylanisole, is outlined in Scheme 3. The first four steps in the synthetic sequence follow those used in the reported preparation of the 7,s-dimethyl triene 3 (8). Although the ketone 18 could be converted to the COT 21 via the Shapiro reaction, it was found that the subsequent photo-conversion of 21 to the desired triene 20 was excessively slow (e.g., the production of ca.…”
Section: (24% Yield)mentioning
confidence: 99%
“…The structural assignment of triene 20 was based on comparison of its N M R spectral data with those of the known 7,s-dimethyl analogue 3; the chemical shifts of corresponding protons were within 6 0.15, and coupling constants between corresponding protons were identical (8). Supporting evidence for structure 20 was obtained from its thermal reactivity.…”
Section: (24% Yield)mentioning
confidence: 99%
See 1 more Smart Citation